The anti- Leishmaniasis activity of Purified Bacteriocin Staphylococcin and Pyocin Isolated from Staphylococcus aureus and Pseudomonas aeruginosa - Ahmed, Mais E.; Mousa, Issra S.; Al-Halbosiy, Mohammad M.F; Jabar, Entsar (Iraqi Journal of Science, 2018)
Tropical illnesses caused by parasites proceed to cause socioeconomic devastation that reverberate worldwide protozoan parasites, like Leishmania. This parasite has an enormous public health problem in many countries. There is a growing requisite for new control methods for many of these illnesses due to the increasing drug resistance showed by the parasites and problems with drug poisonousness. In this study, fifty-five patients (burns and wounds) were collected from patients from Al-Yarmouk Hospital and Teaching Baghdad Hospital during the period from November, 2015 to January, 2016. Cultural and morphological characteristic examination, biochemical tests were conducted and confirmed the diagnosis by antibiotics sensitivity test and Vitek-2 system. The results identified thirty-three Staphylococcus aureus and thirty Pseudomonas aeruginosa from skin burn and wounds. Vitek 2 system gave confirmation of positive results for both strains with a probability 98-99%. The S. aureus isolate (S3) and P. aeruginosa (P 5) was chosen among bacterial isolates as a good producer for crude both bacteriocins according to their widest inhibition zone by well diffusion assay WDA. Two steps method extraction were used for bacteriocin purification, first via ammonium sulphate at 70% and next step by Sephadex G-50 gel filtration chromatography. The two new drugs staphylococcin and pyocin at different concentrations was used for the treatment of L. tropica and L. donvani. All concentration of Staphylococcin showed no inhibitory activity on promastigotes of L. tropica and L. donvani. While the concentration of 32.5 µgmL-1 of pyocin showed the maximum cytotoxic effect on promastigotes of L. tropica and L. donovani, where the inhibition rate (IR%) were 87.1% and 87.9% respectively. As part of the research objectives is the discovery of new treatments against leishmaniasis also benefit from improved models.